2021
DOI: 10.2147/ott.s319300
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on the Pathogenesis of Colorectal Cancer by Constructing a Hsa-circRNA-0067835-miRNA-mRNA Regulatory Network

Abstract: Background: Increasing evidence shows that circular RNAs (circRNAs) play a key role in the development of colorectal cancer (CRC). An interesting candidate RNA in this context is hsa-circRNA-0067835 (circIFT80), but its network of actions is still unclear. Methods: Big data mining technology was used to explore the downstream microRNAs (miRNA) and messenger RNAs (mRNA) of the circIFT80 network. A regulatory network, comprising circIFT80 and its corresponding miRNAs and mRNAs, was derived to preliminarily explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“… 40 Overexpression of hsa-miR-185-5p occurs in the vitreous of proliferative diabetic retinopathy patients, 41 in the pericardiac adipose tissue of patients with coronary artery disease, 42 and significantly enhances endothelial cell angiogenesis. 43 hsa-miR-197-3p is highly expressed in proliferative diabetic retinopathy patients, 44 , 45 is involved in the development of colorectal cancer 46 and non-small cell lung cancer, 47 and may act as a biomarker for follicular thyroid cancer. 48 Further, hsa-miR-485-5p is associated with lupus nephritis, 49 pulmonary tuberculosis, 50 and cancers such as lung cancer, 51 hepatocellular carcinoma, 52 oral tongue squamous cell carcinoma, 53 and glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“… 40 Overexpression of hsa-miR-185-5p occurs in the vitreous of proliferative diabetic retinopathy patients, 41 in the pericardiac adipose tissue of patients with coronary artery disease, 42 and significantly enhances endothelial cell angiogenesis. 43 hsa-miR-197-3p is highly expressed in proliferative diabetic retinopathy patients, 44 , 45 is involved in the development of colorectal cancer 46 and non-small cell lung cancer, 47 and may act as a biomarker for follicular thyroid cancer. 48 Further, hsa-miR-485-5p is associated with lupus nephritis, 49 pulmonary tuberculosis, 50 and cancers such as lung cancer, 51 hepatocellular carcinoma, 52 oral tongue squamous cell carcinoma, 53 and glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has supported that circRNAs participate in regulating tumorigenesis and drug resistance of CRC ( 100 , 101 ). Chen et al.…”
Section: Circrnasmentioning
confidence: 99%
“…For example, lncRNA TUG1 can promote the growth and migration of CRC cells by secreting miR-145-5p, and the TUG1/miR-145-5p/TRPC6 pathway can serve as a target for CRC diagnosis and therapy (113). Liu et al showed that the circIFT80/hsa-miR-370-3p/WNT7B signalling axis might also play a role in carcinogenesis (114). CircIFT80 inhibits the expression of hsa-miR-370-3p in CRC cell lines, thereby inhibiting apoptosis.…”
Section: Therapeutic Target and Microrna Therapymentioning
confidence: 99%
“…Liu et al. showed that the circIFT80/hsa-miR-370-3p/WNT7B signalling axis might also play a role in carcinogenesis ( 114 ). CircIFT80 inhibits the expression of hsa-miR-370-3p in CRC cell lines, thereby inhibiting apoptosis.…”
Section: Clinical Applicationsmentioning
confidence: 99%